2022
DOI: 10.3390/ijerph192114007
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis and Peritoneal Dialysis in Germany from a Health Economic View—A Propensity Score Matched Analysis

Abstract: Background: Hemodialysis (HD) and peritoneal dialysis (PD) are deemed medically equivalent for therapy of end-stage renal disease (ESRD) and reimbursed by the German statutory health insurance (SHI). However, although the home dialysis modality PD is associated with higher patient autonomy than HD, for unknown reasons, PD uptake is low in Germany. Hence, we compared HD with PD regarding health economic outcomes, particularly costs, as potentially relevant factors for the predominance of HD. Methods: Claims dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The majority of studies included patients from Europe. The patient collective is similar to the German collective [8].…”
Section: Qalymentioning
confidence: 89%
See 1 more Smart Citation
“…The majority of studies included patients from Europe. The patient collective is similar to the German collective [8].…”
Section: Qalymentioning
confidence: 89%
“…Data regarding mortality and healthcare costs, including transportation, were extracted from a paper by Shukri et al [8]. They analyzed claims data from two large German health insurance companies.…”
Section: Data Collectionmentioning
confidence: 99%
“…When studying mental and physical health associated with interpersonal violence, PSM was used to select a control group similar to the victim at risk, thereby excluding bias from comparison with the general population [10]. In a health economics study, which concluded that randomization was not possible in retrospective cohort studies, matching techniques such as PSM provided an alternative to generating comparable groups by adjusting for observed confounding factors [11]. In examining the relationship between cancer in adolescents and their healthy quality of life, PSM was used to control for predisposing and contributing factors [12].…”
Section: Introductionmentioning
confidence: 99%